A case report of successful liver retransplantation in patient with early hepatic artery thrombosis complicated by bile ducts necrosis and sepsis - D. A. Granov; A. A. Polikarpov; I. I. Tileubergenov; V. N. Zhuikov; A. V. Moiseenko; A. R. Sheraliev; I. G. Kardanova (Вестник трансплантологии и искусственных органов, 2019)
In this present case report during liver transplantation a patient was developed dissection of hepatic artery (HA) which was noticed after arterial reconstruction step. In one hour after surgery at intervention operating room stent placement of HA was performed. At early postoperative period by hepatic angiography study indicated for a second stent placement of HA, also embolization of splenic artery to treat a steal syndrome. After 2 weeks a patient developed thrombosis of recently placed stents which was required vascular reconstruction of HA by using autovenous graft. The condition complicated by development of a cholangiogenous hepatic abscesses and sepsis despite of all used possible methods of liver graft revascularization. However, used methods of vascular correction, which combined of timely carried out intensive care and antibiotic therapy according microbiology laboratory results allows saving graft function. After treatment of septic complications and patient’s somatic status stabilization and normalization of laboratory results liver retransplantation was performed.